Analisis Perilaku Konsumen Muslim dalam Berbelanja Melalui TikTok Shop - Aisah, Siti; Astutiningsih, Sri Eka; Estiningrum, Sri Dwi; Maimuna, Nadya Amalia (Comprehensive Journal of Islamic Studies, 2025)
This study aims to examine the shopping behavior of Muslim consumers on the TikTok Shop platform from an Islamic perspective. This study employs a qualitative methodology utilizing a field research approach, where data is collected directly from the research setting. Field research is research in which data and information are obtained through observation, interviews and documentation. The subjects in this study were Z generation in Patranrejo Village, Berbek District, Nganjuk Regency. The results of this study show that (1) Consumption behavior in shopping Z generation in Patranrejo Village prefers to shop online because of the large selection of goods, easy, and affordable prices. 2) The seven informants, two of whom already have a plan to allocate funds for expenditure, while the remaining five informants do not have an allocation of funds for shopping. (3) Consumer shopping patterns on TikTok social media come from the intensity of watching videos and live streaming that offer promo prices that lead to product purchases. Based on the findings of this study, it is recommended that Muslim consumers adhere to the principles, ethical guidelines, and consumption boundaries outlined in Islamic teachings when engaging in shopping activities.